APLIKASI SIX SIGMA DAN KAIZEN UNTUK MENGURANGI CACAT PRODUK - alan, Alan Roso Dewanto; Ari Zaqi Al Faritsy (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Minomartani Sleman village is the location of Bakpia X MSMEs, which make dry and wet bakpia of various flavors. However, until now, bakpia products produced are still many defects stuffing out, burnt, and bulging. The purpose of this study was to determine the factors that cause disability to occur and efforts to improve it. This study uses Six Sigma method with DMAIC (Define, Measure, Analyze, Improve, and Control) and proposed improvements with Kaizen. The results of DMAIC analysis showed that the three product defects were caused by human factors, materials, methods, and machines. Sand defects amounted to 276 items, or 49.8%, 110 items, or 19.9%, and defects in bakpia filling out amounted to 168 items, or 30.3%. On the human factor, for example, forget turning bakpia. The factor of the machine or tool is uneven heat in the pan. The mixing process is uneven, and the baking sheet is sticky. Method factor because there is no SOP in MSMEs. Material factors the problem of green beans are not good.